Intellectual Capital and Capital Structure: Does It Shape the Value of the Insurance Firms? - Muhammad Agusalim; Tasrim Tasrim; Wahda Wahda (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
This study aims to explore the relationship between intellectual capital and capital structure that shaping the value of insurance firms listed on the Indonesia Stock Exchange, using corporate financial statement data. Descriptive statistics and multiple regression analysis were used. This study provides an overview of the importance of managing intellectual capital (human capital, capital structure and relation capital) in shaping firm’s value. Agents are an inseparable part of intellectual capital (intangible assets) and are very meaningful in the firm's operations. The result indicates that intellectual capital and capital structure shaping the firm's value. It also provides information about the relationship of capital structure and firm’s value, especially in MM theory (tax), but the firms need to look at trends off the use of debt in their capital structure.